Evaluation of Metal-Active Gas Double-Sided Double-Power Arc Welded Joints of High-Strength Low-Alloy Steel - Chen, Y.X.; Yang, C.D.; Wang, X.J.; Chen, S.B. (Проблемы прочности, 2015)
High-strength low-alloy steel 50 mm thick is well joined by metal-active gas double-sided doublepower arc welding, which does not require preheating, postheating, and back chipping. Mechanical properties of the weld seam and base metal were investigated. Results of the tensile test indicate that the strength of the weld seam is about 862.73 MPa and its average elongation is 20.74%. The hardness of the base metal and weld zone is 299 and 361 HV, respectively. The maximum hardness (395 HV) is observed in the heat-affected zone. The average toughness of the face and root sides of the weld center is 75 and 71 J, respectively.